2023
DOI: 10.1177/23779608221150717
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Practices of Hypertensive Patients Towards Stroke Prevention Among Rural Population in Saudi Arabia: A Cross-Sectional Study

Abstract: Introduction Stroke is a significant health problem and is considered one of the leading causes of mortality and permanent disability worldwide. Hypertension is a primary risk factor for stroke. Thus, hypertensive patients’ knowledge, attitudes, and practices (KAP) are essential in preventing stroke. Objective To examine hypertensive patients’ KAP towards stroke prevention among rural population in Saudi Arabia. Methods The study utilized a cross-sectional design. The data were collected using a convenience sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 48 publications
0
0
1
Order By: Relevance
“…Regarding attitudes, the ndings of this study revealed that 40.8% of the participants had a positive attitude toward stroke prevention [95% CI (35.7%, 45.8%], which is lower than that reported in previous studies in Saudi Arabia (64.3%) (30) and South India (73.8%) (15). The practical reason for this discrepancy may be the small sample size.…”
Section: Discussioncontrasting
confidence: 74%
“…Regarding attitudes, the ndings of this study revealed that 40.8% of the participants had a positive attitude toward stroke prevention [95% CI (35.7%, 45.8%], which is lower than that reported in previous studies in Saudi Arabia (64.3%) (30) and South India (73.8%) (15). The practical reason for this discrepancy may be the small sample size.…”
Section: Discussioncontrasting
confidence: 74%
“…The study's participants stated that they are fully aware that strokes can be prevented and cause death. However, according to a prior study, they are unsure of how to adequately prevent it [17]. In addition, individuals at high risk of stroke do not follow prevention advice even when medical professionals verbally advise them to do so [18].…”
Section: Discussionmentioning
confidence: 99%
“…Primary prevention of stroke is better and cheaper than treatment of stroke and the global cost of strokes is an average of between €610-€220,822.45 based on the cost of the illness (Lucas-Noll, et al, 2023). Good awareness and knowledge of stroke, risk factors, and warning signs are vital for early practice of stroke prevention (Alhowaymel, et al, 2023). Therefore, in this study, we sought to investigate sociodemographic predictors of knowledge and practice of stroke preventive strategies among Healthcare workers in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, in effect, the management of stroke depends mainly on the public's knowledge of its warning signs, which could aid in earlier detection and better response rates (Kalehoff, & Oparil, 2020;Sayyad, et al, 2021). Consequently, it is important to measure individual patients' knowledge, attitudes, and practices (Alhowaymel, et al, 2023) (KAP) towards stroke prevention among the general population and explore the factors that may contribute to the KAP levels. Generally, people residing in the communities have less access to healthcare services.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation